Immunologic mechanisms in the adaptation of swine farm workers to their work environment. Issue 4 (August 2013) - Bønløkke, Jakob H; Cormier, Yvon; Veillette, Marc; Radu, Arnold; Mériaux, Anne; Duchaine, Caroline
Swine building exposure causes inflammatory reactions that appear to be attenuated with prolonged periods of contact. The mechanisms behind this adaptation to a dusty and endotoxin-rich environment are poorly understood. Our aim was to compare levels of selected inflammatory mediators in swine farm workers at times with differences in exposure. Participants had blood sampling done before and after each of three work shifts—two in winter and one in summer. Before one of the winter visits they had avoided pulmonary exposure to the swine buildings by wearing respiratory protection for 4 d. The other visits were done after non-protected periods of work. Protein and mRNA concentrations were measured in blood. Mixed models were used for the statistics. During summer higher concentrations of mRNA to IL-8, lymphocyte function-associated antigen 1 and bactericidal/permeability-increasing protein (BPI) were observed. BPI mRNA increased only over the work shift after the unprotected winter period ( P  = 0.039). BPI decreased from elevated levels across the shift after use of respiratory protection ( P  = 0.003), but was unchanged during the other two visits. The findings suggest possible roles for these proteins in adaptation to the swine building environment after repeated exposures.